2017
DOI: 10.5455/msm.2017.29.219-227
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Characteristics of Collections of Folk Recepies in the Folk and Traditional Medicine of Bosnia and Herzegovina

Abstract: Introduction:Folk medicine represents part of the folk culture, when we first think about the rural culture with characteristic of the rural population in the pre-industrial period. The difference between official and folk medicine is manifested in the education, knowledge and social status of those practicing folk medicine as well as their patients. The most common ways of treating were the treatment by use of herbs, magic and treatments based on religious beliefs. So, it is of no surprise that folk medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…53 In many cases, despite the absence of robust evidence for their effectiveness, custom and folk religion shape people's traditional medical care practices. 54 In Southeast Asia, cancer patients (including female reproductive cancers such as breast and cervical cancers) spend a considerable amount of money on traditional local medicine. 55 A study from an African country reported the use of traditional medicine for the prevention and treatment of cervical cancer.…”
Section: Beliefs In Traditional Local Remediesmentioning
confidence: 99%
“…53 In many cases, despite the absence of robust evidence for their effectiveness, custom and folk religion shape people's traditional medical care practices. 54 In Southeast Asia, cancer patients (including female reproductive cancers such as breast and cervical cancers) spend a considerable amount of money on traditional local medicine. 55 A study from an African country reported the use of traditional medicine for the prevention and treatment of cervical cancer.…”
Section: Beliefs In Traditional Local Remediesmentioning
confidence: 99%
“…Oceania grapples with non-science-based treatments and fraudulent medical claims (Table 3). 3, In the European region, with respect to legality, governments have begun to establish clear boundaries between quackery and unauthorised healthcare providers.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional healing practices exclusively carried out by women, particularly those who have reached menopause. This is based on popular beliefs that only "pure" women possess the ability to treat unwell individuals [3].…”
Section: Bosnia and Herzegovinamentioning
confidence: 99%
See 1 more Smart Citation